Nine new species of the Eremobates scaber species group of the North American camel spider genus Eremobates (Solifugae, Eremobatidae) - Cushing, Paula E.; Brookhart, Jack O. (Zootaxa, 2016)
Nine new species of the Eremobates scaber species group of the solifuge genus Eremobates Banks 1900 are described, eight of them from Mexico. These new species are: E. axacoa, E. bonito, E. cyranoi, E. fisheri, E. hidalgoana, E. jaliscoana, E. minamoritaana, E. zacatecana, and E. zapal and together increase the size of this species group to 23. A key to all species in the E. scaber species group is also provided.